2013
DOI: 10.1038/srep01672
|View full text |Cite
|
Sign up to set email alerts
|

Metal/dielectric/metal sandwich film for broadband reflection reduction

Abstract: A film comprising randomly distributed metal/dielectric/metal sandwich nanopillars with a distribution of cross-sectional diameters, displayed extremely low reflectance over the blue-to-red regime, when coated on glass and illuminated normally. When it is illuminated by normally incident light, this sandwich film (SWF) has a low extinction coefficient, its phase thickness is close to a negative wavelength in the blue-to-red spectral regime, and it provides weakly dispersive forward and backward impedances, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Sang-Hwan et al fabricated a 4-layer dielectric-metal-dielectric-metal structure, which showed 99.3% average absorbance in the visible spectrum 11 . Jen et al fabricated metal-dielectric-metal pillars on a glass substrate with an absorbance of 80% and 40% for light with a wavelength of 400 nm and 800 nm, respectively 12 .…”
mentioning
confidence: 99%
“…Sang-Hwan et al fabricated a 4-layer dielectric-metal-dielectric-metal structure, which showed 99.3% average absorbance in the visible spectrum 11 . Jen et al fabricated metal-dielectric-metal pillars on a glass substrate with an absorbance of 80% and 40% for light with a wavelength of 400 nm and 800 nm, respectively 12 .…”
mentioning
confidence: 99%
“…Accomplished by an ARC on the front face of the solar cell [93], [94], this is a cost-effective way to increase the efficiency because coating techniques are highly developed in the optics industry [95]. Multilayered ARCs are being designed and tested towards broadband, polarization-insensitive, and omnidirectional reduction of reflection [96]- [98].…”
Section: Light-management Designsmentioning
confidence: 99%
“…In recent years, the research of electromagnetic (EM) metamaterials (MMs) has been increased rapidly. MMs have been designed and fabricated to perform novel properties, such as negative refractive index [1,2], electromagnetically induced transparency [3,4], super-lensing [5], perfect absorption [6] and cloaking [7]. One major advantage of MMs over natural materials is that their macroscopic parameters can be designed to have desired values.…”
Section: Introductionmentioning
confidence: 99%